2016
DOI: 10.1186/s12917-016-0815-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of ketamine and antinociceptive effects of ketamine and ketamine-lidocaine infusions in conscious dogs

Abstract: BackgroundCentral sensitization is a potential severe consequence of invasive surgical procedures. It results in postoperative and potentially chronic pain enhancement. It results in postoperative pain enhancement; clinically manifested as hyperalgesia and allodynia. N-methyl-D-aspartate (NMDA) receptor plays a crucial role in the mechanism of central sensitisation. Ketamine is most commonly used NMDA-antagonist in human and veterinary practice. However, the antinociceptive serum concentration of ketamine is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…A study of Bergadano et al (2009) [54], investigating the analgesic effects of a low-dose constant rate infusion of ketamine, showed that ketamine's antinociceptive effects were evident when plasma concentrations ranged between 220-370 ng/mL. Another study investigating antinociceptive effects of different ketamine infusion regimes found that the serum concentration of ketamine to produce mechanical antinociceptive effects is above 200 ng/mL [55]. In the present study, mean Cmax after IN administration was 1694.48 ng/mL and mean plasma concentrations stayed above 200 ng/mL until 2 h after ketamine administration, indicating antinociceptive effects in this time frame.…”
Section: Table 2 Pharmacokinetic Parameters Of Ketamine In Dogs Admimentioning
confidence: 99%
“…A study of Bergadano et al (2009) [54], investigating the analgesic effects of a low-dose constant rate infusion of ketamine, showed that ketamine's antinociceptive effects were evident when plasma concentrations ranged between 220-370 ng/mL. Another study investigating antinociceptive effects of different ketamine infusion regimes found that the serum concentration of ketamine to produce mechanical antinociceptive effects is above 200 ng/mL [55]. In the present study, mean Cmax after IN administration was 1694.48 ng/mL and mean plasma concentrations stayed above 200 ng/mL until 2 h after ketamine administration, indicating antinociceptive effects in this time frame.…”
Section: Table 2 Pharmacokinetic Parameters Of Ketamine In Dogs Admimentioning
confidence: 99%
“…Continuous IV infusion of maropitant, lidocaine, or ketamine alone promoted an antinociceptive effect. In dogs, continuous infusions of ketamine and lidocaine alone or in combination or with other drugs induce antinociceptive effects and decrease analgesic requirements [ 7 , 37 ]. The groups that received combinations did not significantly differ from the group that received only maropitant.…”
Section: Discussionmentioning
confidence: 99%
“…A technique used in mastectomy is intermittent bolus administration and continuous infusion of ketamine and lidocaine. This protocol provides a constant concentration of these drugs, faster recovery, and normalization of plasma levels [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%